Date (Phoenix dactylifera L. cv. Medjool) Seed Flour, a Potential Ingredient for the Food Industry: Effect of Particle Size on Its Chemical, Technological, and Functional Properties - Nuria Muñoz-Tebar; Laura Candela-Salvador; José Ángel Pérez-Álvarez; José Manuel Lorenzo; Juana Fernández-López; Manuel Viuda-Martos (Plants, 2024)
The objective of this work was to evaluate the effect of particle size on the chemical composition, fatty acid and polyphenol profile, physicochemical and techno-functional properties, and antioxidant capacity of flour obtained from date seeds. The date seed flours obtained had a high content of total dietary fiber (67.89–76.67 g/100 g), and the reduction in particle size decreased the moisture and protein contents, while the fat, mineral (Ca, Fe, Zn, and Mg), and fatty acid contents were significantly increased, with oleic acid being the highest. Water activity increased with decreasing particle size, and the finest flour (<210 mm) tended to be yellowish and reddish. The water- and oil-holding capacities decreased in the flours with the smallest particle size compared to the largest sizes. The main polyphenolic compounds in all the samples were catechin, epicatechin, and epigallocatechin-3-gallate. The antioxidant activity significantly improved with reductions in the particle size of the date seed flour, with the ABTS, DPPH, and FRAP values ranging between 8.99 and 20.68, 0.66 and 2.35, and 1.94 and 4.91 mg Trolox equivalent/g of date seed flour. The results of the present study suggest that the flour obtained from date seeds cv. Medjool can be a valuable co-product for the food industry due to its fiber content, essential fatty acids, and bioactive compounds that can help reduce the amount of waste generated, promoting the circular economy in the food chain.